2006
DOI: 10.1088/0031-9155/51/4/n01
|View full text |Cite
|
Sign up to set email alerts
|

The use of a simulated body shape for determination of patient dosimetry within whole body ultraviolet treatment cabinets

Abstract: Details are described of a simulated body shape utilized to determine patient dosimetry within whole body ultraviolet treatment cabinets. The body shape was designed to have a shape characteristic of the patient group undergoing treatment and was utilized in several Waldmann whole body treatment cabinets and with irradiance measurements undertaken using a Bentham DM150C spectroradiometer. It was considered that the rigid defined structure of the body shape allowed satisfactory reproducibility of measurements i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Especially problematic are types reliant on monitoring a small number of lamps . More recent types compensate reasonably well for differences in the amount of shielding of the fluorescent tubes by patients of differing sizes . However, it should be recognized that internal dosimeters monitor the UV that is reflected from a relatively small area of skin and do not measure the average irradiance to the whole patient.…”
Section: Phototherapy Equipmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Especially problematic are types reliant on monitoring a small number of lamps . More recent types compensate reasonably well for differences in the amount of shielding of the fluorescent tubes by patients of differing sizes . However, it should be recognized that internal dosimeters monitor the UV that is reflected from a relatively small area of skin and do not measure the average irradiance to the whole patient.…”
Section: Phototherapy Equipmentmentioning
confidence: 99%
“…It has been shown that cabins fitted with a pair of detectors are less susceptible to this type of dose error than cabins with single detectors …”
Section: Phototherapy Equipmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Variable factors that are difficult to control are connected to regional body differences in UV sensitivity, which may account for a factor of 1.5 not considering palms and soles (13, 14). It is also important to recognize that the intensity of UV is uneven in a given cabin, mostly because the radiation is only coming from one side on the lower legs and in the face compared with mid area; this may represent a factor of about 1.3 (15). A small variation can also be attributed to the variation in electricity current highly depending on the geographical site and cabin temperature (2) (Table 3).…”
Section: Uncontrollable Factorsmentioning
confidence: 99%
“…the skin) from the UV lamps, which is affected by patient position in the UV cabinet and body shape and size (6). Clarkson et al also concluded that the accuracy of cabinet dosimetry can be dependent on patient size (7). UV dosing is calculated using designated patient irradiance, which is determined by measuring mean irradiance at chest, waist and knee levels in a person of average body size (8).…”
mentioning
confidence: 99%